2011
DOI: 10.1521/jscp.2011.30.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Do Shattered Worldviews Lead to Complicated Grief? Prospective and Longitudinal Analyses

Abstract: Theories of complicated grief (CG) and posttraumatic stress disorder (PTSD) posit a central etiological and maintaining role for global beliefs about the world (Janoff-Bulman, 1992). in two studies using separate bereaved samples, we examined these theoretical postulates. Study 1 included prospective data on bereaved spouses and nonbereaved controls at baseline and 6-months post-loss. high pre-loss justice beliefs and acceptance of death prospectively predicted lower depression in bereaved but not control part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 52 publications
2
49
1
Order By: Relevance
“…Thus, social support (SS) counted on by a person in mourning, may be a matter of much importance in the early stages, of softening and cushioning the impact of the death of a loved one (damping effect), as well as in the final stages of assisting the improvement and recovery of the bereaved (recovery effect) (Lobb et al, 2010;Mancini, Prati & Bonanno, 2011;Stroebe, Wech, Stroebe & Abakoumkin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, social support (SS) counted on by a person in mourning, may be a matter of much importance in the early stages, of softening and cushioning the impact of the death of a loved one (damping effect), as well as in the final stages of assisting the improvement and recovery of the bereaved (recovery effect) (Lobb et al, 2010;Mancini, Prati & Bonanno, 2011;Stroebe, Wech, Stroebe & Abakoumkin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…He feels that the isolating experience of pain is not only unbearable, but more distressingly, it is unfair. Mancini et al (2011) find that a pre-established negative worldview will more likely be confirmed by another traumatic event. This heightens a sense of threat, and the bereaved, as in the case of Jacob, may feel even more powerless.…”
Section: Working Around Jacob's Laddermentioning
confidence: 75%
“…He did not just lose a bedridden, weakened person to be cared for; he lost the gal who made him feel weak at the knees with a flashing smile on their first date. Mancini, Prati, and Bonanno (2011) extend the meaning of loss to a worldview, which is a global belief that influences how one appraises and responds to stressors. A worldview may have either buffering or shattering effects.…”
Section: Working Around Jacob's Laddermentioning
confidence: 99%
See 1 more Smart Citation
“…This account of posttraumatic states does not require the related schemas to differ qualitatively from those of depressive or anxious states but only to appear in new contexts and challenge existing implicit accounts of the world or the self. Accordingly, the prevalence of shattered assumptions may be observed in states that are typically associated with depressive pathologies, such as mourning [30] and neuroticism [17], where the irruptive quality of the negative schemas progressively fades. If this interpretation is correct, the SST failed to provide evidence on the activity of trauma-related schemas because these schemas are similar to those observed in affective disorders, while the specificity of trauma derives from its structural impact on a previous schematic organization.…”
Section: Discussionmentioning
confidence: 99%